Culture Shock In Intercultural Communication Between Foreign Students In Jakarta - Sigalingging, Adelina Jesica Angel; Idaman, Nur (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Cultural differences can lead to culture shock and anxiety among those who participate in intercultural communication. Migrant students are one illustration of students who have faced culture shock since choosing to study in Jakarta. This study intends to describe the Culture Shock of Intercultural Communication among Overseas Students in Jakarta. The purpose of this study is to find out how the stages of culture shock and communication barriers experienced by overseas students in Jakarta are in intercultural interactions. The theory applied in this study is the stages in culture shock, namely the honeymoon phase, the crisis phase, the adjustment phase, the bhicultural phase and Anxiety/Uncertainty Management Theory (AUM). Anxiety/Uncertainty Management Theory (AUM) is a theory that discusses a person’s experience of anxiety and uncertainty that arises when dealing with strangers or meeting people with different cultures from him in Jakarta. This study uses a qualitative approach with descriptive research type, the types of data used are primary and secondary data, with data collection techniques using interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, conclusion drawing. The validity of the data used is source triangulation. The results of this study indicate that all informants who are overseas students in Jakarta experience four stages in culture shock, namely the honeymoon phase, the crisis phase, the adjustment phase, the bicultural phase and anxiety/uncertainty management (AUM). The second informant, Melan, does not experience anxiety at all, because Melan admits that she likes to mingle with new people. The culture shock and anxiety experienced by overseas students in Jakarta did not really cause a sense of hopelessness. Various feelings of discomfort experienced by overseas students in Jakarta will be eroded by itself with the passage of time which makes overseas students adapt to their environment. The obstacles in the interaction process of immigrant students come from within, habits, and language. For each individual who will travel overseas, first seek information from reliable sources regarding the social and cultural situation in the area so as not to experience culture shock